2014
DOI: 10.5603/ait.2014.0004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral gabapentin on haemodynamic variables during microlaryngoscopic surgery

Abstract: 800 mg oral gabapentin given 90 min before a procedure attenuates the rise of diastolic blood pressure and mean arterial blood pressure in the first 15 min after microlaryngoscopy surgery, but has no effect on systolic blood pressure or heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…They found that gabapentin is effective in reducing the painful stimuli during laryngoscopy and intubation, hence attenuating the haemodynamic response which correspondent to our study [22].…”
Section: Discussionmentioning
confidence: 51%
“…They found that gabapentin is effective in reducing the painful stimuli during laryngoscopy and intubation, hence attenuating the haemodynamic response which correspondent to our study [22].…”
Section: Discussionmentioning
confidence: 51%
“…Ayatollahi and his colleagues have reported that administration of 800 mg of oral gabapentin 1.5 hours prior to surgery was effective in the attenuation of both diastolic and mean arterial pressure. However, both systolic blood pressure and heart rate were not significantly affected [12].…”
Section: Discussionmentioning
confidence: 79%
“…Various drugs such as propofol,[ 8 9 ] sevoflurane,[ 9 ] oral clonidine,[ 10 ] lignocaine spray,[ 2 ] β-blockers,[ 11 ] and oral gabapentin[ 12 ] have been used in various combinations and doses to ameliorate this hyperdynamic response to MLScopy. However, a delayed postoperative awakening with propofol, delayed onset of action with oral clonidine and gabapentin and an increased incidence of complications secondary to myocardial depression with β-blockers were faced.…”
Section: Discussionmentioning
confidence: 99%